Os pais como mediadores do relacionamento avós e netos. - Aureliano, Rodrigo de Oliveira (2022)
The greater permanence, due to longevity, of people in the role of grandparents has raised interest in research and observation of the relationships between grandparents, grandchildren and parents. Thus, this research aimed to analyze the mediation of parents in the relationship between grandparents and grandchildren. Specifically, its objectives were: to know the practices of parents' mediation in the interaction between grandparents and grandchildren; identify who takes the initiative in this interaction; to verify how parents perceive the influence of grandparents in their grandchildren's lives; to find out if the mediation changes as the grandchildren grow up; capture if there are conflicts in this relationship and understand how they are resolved. Two fathers and five mothers participated, making a total of seven individuals, married or in a stable union, heterosexual, aged between 40 and 67 years, of middle social class, with children in different age groups and who did not live with their grandparents. . A biosociodemographic questionnaire and a semi-structured interview script were used. The results were analyzed using the Thematic Content Analysis Technique. The main results of the research point out: 1) parents identify mediation in mutual care and protection; 2) the initiative comes from both generations; 3) parents perceive a greater influence on the children's language, respect and empathy with the elderly, in dealing with technology and with differences as positive points of the intergenerational relationship; 4) there are conflicts, these arise from differences in visions and generations, rigidity on the part of a grandfather, grandparents' interference in raising children, preference and comparisons between grandchildren, as well as the religious influence of grandparents, and solutions are sought as dialogue with grandchildren and grandparents, distance and rapprochement and in some cases reveal what happened in order to maintain balance; 5) the changes that have taken place in the relationship over time result from the greater maturity and independence of the grandchildren, who start to protect the grandparents; 6) the parents were unanimous in affirming their mediation as essential in this relationship. It is hoped with this research to give visibility to the mediation of parents for the relationship between grandparents and grandchildren, which is still little focused in intergenerational studies.